Les propositions de la revue à mi-parcours de la PAC sont explicitées - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2003)
Le Commissaire pour l'agriculture Franz Fischler a...